Pentingnya Memahami Hadist Pendidikan Dalam Menanamkan Nilai-Nilai Moral Melalui Metode Kisah Pada Pembelajaran Agama Islam - Muhammad Zulkhaidir; Sawaluddin Siregar (Jurnal Pendidikan Tuntas, 2023)
This research aims to explore the importance of understanding hadith in designing Islamic and progressive learning methods. This research will discuss the relevance of hadith as a teaching source in the context of Islamic education and its impact on the development of learning methods that integrate Islamic values ​​and progressive concepts. This research will look at the extent of the contribution of hadith in forming a broad and comprehensive learning paradigm, covering scientific, moral and social aspects. Apart from that, this research also identifies challenges and opportunities in integrating hadith into learning methods that are appropriate to current developments. It is hoped that the results of this research can contribute to a deep understanding of the importance of hadith in the context of modern Islamic education and provide a basis for developing learning methods that are more effective and relevant to Islamic values ​​and the demands of the times. Keywords:  Understanding Hadith, Story Methods, Islamic Education